Determination of interfacial properties of cellulose nanocrystal-modified sisal fibre in epoxy by cyclic single-fibre pull-out - Zhang, Z.; Li, Y.; Fu, K.; Li, Q.
To examine the effects of surface modification on the interfacial properties, the surface of sisal fibres was modified by rod-like cellulose nanocrystals (CNCs)with length-to-diameter ratios ranging from 20 to 33, which were prepared using an electrophoretic deposition method. An effective method was proposed for measuring the interfacial properties of sisal fibre/matrix, including interfacial fatigue strength and toughness, via cyclic single-fibre pull-out with the aid of dynamic mechanical analyser (DMA). It was found that the interfacial fatigue shear strength of the CNC-modified sisal fibre/epoxy specimens was 6.6 MPa, 1.2 times greater than that of specimens without treatment. Moreover, the interfacial toughness 9.34 J/m2 of the CNC-treated sisal fibre/epoxy specimens increased by 51 percent compared to that of the untreated specimens. It was indicated that pull-out of the CNCs with a large aspect ratio was the main toughening mechanism for CNC-modified sisal fibre/epoxy interface.
Keywords: INTERFACIAL FATIGUE STRENGTH; TOUGHENING MECHANISM; SISAL FIBRE; CELLULOSE NANOCRYSTAL; CYCLIC FIBRE PULL-OUT